2011
DOI: 10.1590/s0034-737x2011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Profundidade de sulco, área de solo mobilizada e força de tração de uma semeadora-adubadora em razão da velocidade de deslocamento

Abstract: RESUMOProfundidade de sulco, área de solo mobilizada e força de tração de uma semeadora-adubadora em razão da velocidade de deslocamento Este trabalho teve por objetivo avaliar a profundidade de sulco, área de solo mobilizada e a força de tração solicitada por uma semeadora-adubadora de precisão em sistema de plantio direto na cultura do milho, em razão da velocidade de deslocamento. O delineamento experimental foi em blocos ao acaso, com quatro repetições em arranjo fatorial 4 x 3, com 12 tratamentos, constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
4
0
4
Order By: Relevance
“…The interaction between furrow opener and speed had a significant effect on maximum depth only for the hoe opener, with values between 0.12 and 0.01 m for the first three levels (1.11, 1.67 and 2.22 m/s), with significant reduction under the effect of higher speed, when depth was 0.10 m. The mismatched double-disc yielded an average depth of 0.07 m for the tested speeds. Silveira et al (2011), while evaluating furrow depth by a hoe during maize seeding, also identified reduction of this variable when increasing seeding speed. The authors stressed that this behavior is due to the fact that the hoe furrow opener tends to move closer to the surface at higher speeds, and the possible causes for this variation are penetration resistance, soil moisture and roughness.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The interaction between furrow opener and speed had a significant effect on maximum depth only for the hoe opener, with values between 0.12 and 0.01 m for the first three levels (1.11, 1.67 and 2.22 m/s), with significant reduction under the effect of higher speed, when depth was 0.10 m. The mismatched double-disc yielded an average depth of 0.07 m for the tested speeds. Silveira et al (2011), while evaluating furrow depth by a hoe during maize seeding, also identified reduction of this variable when increasing seeding speed. The authors stressed that this behavior is due to the fact that the hoe furrow opener tends to move closer to the surface at higher speeds, and the possible causes for this variation are penetration resistance, soil moisture and roughness.…”
Section: Resultsmentioning
confidence: 95%
“…Casão Júnior et al (2000) and Silveira et al (2011) evaluated the influence of operating speed on maize sowing with a row crop planter fitted with the hoe opener, and concluded that furrow depth was reduced by operating speed and that the soil disturbance area was increased with higher speed. Cepik et al (2005), when evaluating the volume of soil disturbance by a row crop planter with five lines, fitted with hoe openers, according to the speed, found a mean value of 121.80 and 135.90 m³/ha, showing a 12% increase when sowing speed went from 1.25 m/s to 1.81 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, Germino e Benez (2006), concluíram que a presença de disco não modifica as exigências de tração por hastes sulcadoras, sendo de 0,77 kN para situações com disco e 0,78 kN para as condições sem o mecanismo. Silveira et al (2011), avaliando o desempenho operacional de uma semeadora-adubadora em diferentes manejos da cobertura do solo e em função da velocidade de deslocamento, observaram que o aumento desta proporcionou uma redução da força de tração. Por outro lado, Siqueira et al (2001), trabalhando com velocidades de 1,31 e 2,31 m s -1 na semeadura de soja, evidenciaram que a força de tração aumenta de forma significativa com o incremento da velocidade.…”
Section: Introductionunclassified
“…Tabela 3 -Velocidades de deslocamento utilizadas em trabalhos de pesquisa com semeadoraadubadora. FURLANI et al, 2007) Latossolo Soja 4,00 5,00 6,00 (FURLANI et al, 2008) Latossolo Milho 4,74 (GROTTA et al, 2009) Latossolo Milho 4,10 4,10 (MAHL; GAMERO; BENEZ, 2007) Nitossolo Milho 4,40 6,10 8,10 (MERCANTE et al, 2005 Latossolo Milho 5,20 8,40 5,20 8,40 (MODOLO et al, 2004) Latossolo Milho 5,20 8,40 5,20 8,40 (SANTOS;TOURINO, 2008) Latossolo Milho 4,97 6,48 7,99 (SILVEIRA et al, 2011) Latossolo Milho 3,50 4,00 5,50 7,00 (SILVEIRA et al, 2013) Latossolo Milho 3,50 4,00 5,50 7,00 (TRINTIN;…”
Section: Semeadora-adubadora Para Plantio Diretounclassified
“…Em relação ao coeficiente determinístico das demais situações(Figura 22), os valores foram superiores a 0,9 para todas as situações avaliadas, contudo os valores estimados de consumo horário de combustível foram superestimados(Figura 22). As diferenças entre os valores preditos e mensurados para os valores extraídos dos trabalhos Almeida, Silva e Silva (2010),Bortolotto, Neto e Bortolotto (2006),Furlani et al (2007),Mahl, Gamero e Benez (2007),Santos, Volpato e Tourino (2008) eSilveira et al (2011) foram quantificados e divididos em classes (Figura 23). Histograma para diferença entre consumo predito e estimado A variação da diferença entre os valores preditos e mensurados ocorre entre -5,00 e 35,00%, com maior classe de ocorrência entre 20,00 e 25,00%.…”
unclassified